(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2026)
This article systematizes a survey of the cooperative sector in the District of San Martín, Buenos Aires Province, conducted jointly by the municipality, the Union of Workers of the Popular Economy (UTEP), the Idear Ciudad Public Policy Laboratory, and the National University of San Martín. The survey encompasses a diverse set of cooperative experiences in the production of goods and services. The work begins with a theoretical and conceptual analyzis of workers cooperatives. It then explores the characteristics of cooperative experiences and social enterprises in the district, their emergin problems, and current challenges. This situated analysis provides concrete elements for examining the relationship between the State, public policies, and this sector of the economy. Finally, we will analize the current state of cooperativism in light of the government led by Javier Milei (2023-2027) and the conditions that enable the sector.